Gastrointestinal cell injury and perceived symptoms after running the Boston Marathon - Kelly, Melani R.; Emerson, Dawn M.; McDermott, Brendon P.; Atkins, Whitley C.; Butts, Cory L.; Laursen, R. Mark; Troyanos, Christopher; Duckett, Andrew; Siedlik, Jacob (Frontiers in Physiology, 2023)
Gastrointestinal (GI) disturbances are a prevalent cause of marathon related complaints, and in extreme cases can promote life-threatening conditions such as exertional heat stroke. Our aim was to study intestinal cell injury (via intestinal fatty acid binding protein [I-FABP]) and perceived GI distress symptoms among marathon runners. We also examined potential risk factors (e.g., inadequate sleep) that could exacerbate GI disturbances in healthy, trained endurance runners. This was a parallel mixedmethods study design. 2019 Boston Marathon participants were recruited via email and subjects completed surveys before the race describing demographics and training history. Participants